Module Development on Human Breathing System Materials Based on Moocs for Class VIII Students - Setiyowati, Indah (IJOEM Indonesian Journal of E-learning and Multimedia, 2024)
Technology has been used to innovate learning in the contemporary educational system. With the use of technology, teachers hope to create a more engaging learning environment and give pupils stimulus so they can comprehend what they are studying. One form of using technology in learning is the use of MOOCs as a learning medium. Therefore, this research aims to develop a MOOCs-based digital module on respiratory system material for grade VIII junior high school students. This research is a Research and Development (RnD) study with the 4D model which is limited to the third D stage which includes the Define, Design, Development stages. The data collection techniques used were observation, interview, and questionnaire. The instruments used in this study were observation sheets, teacher interview guide sheets, expert validation sheets, and student response test sheets. Data analysis techniques were carried out qualitatively and quantitatively. The results showed that the MOOCs-based digital module was very feasible and could be used based on the results of expert validation. The results of the learner response test to the digital module developed showed a very good category. The conclusion from the results of this study shows that the digital module developed was declared feasible by a team of experts and received a positive response from students to be continued in a wide-scale trial to see the effectiveness of the product.